Pengaruh Price to Book Value, ROE, CR dan DER Terhadap Harga Saham - Saharani, Dina; Diah Febriyanti (Economic Reviews Journal, 2025)
This research investigates the influence of various financial ratios on the stock prices of Pharmaceutical and Health Research companies listed on the Indonesia Stock Exchange over a ten-year period from 2015 to 2024. The main focus is on four key financial indicators: Price to Book Value (PBV), Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER). This research aims to determine how these ratios influence investor perception and ultimately, stock valuation in this specific sector. Through comprehensive data analysis, the findings reveal that PBV does not have a significant impact on stock prices, indicating that market valuation based on book value may not be a primary consideration for investors in this industry. Conversely, ROE shows a positive and significant relationship with stock prices, suggesting that companies generating higher profits relative to shareholders' equity tend to attract more investor confidence. Additionally, CR and DER show varying levels of influence, reflecting the importance of liquidity and leverage in shaping stock performance. Overall, this study provides valuable insights into the financial dynamics affecting pharmaceutical and healthcare companies in Indonesia.